275. Evaluation of Vancomycin Prescribing Quality in Hospitalized Pediatric Patients. (26th November 2018) - Abanyie-Bimbo, Francisca; O'Leary, Erin; Nadle, Joelle; Thompson, Deborah L; Muleta, Daniel; Kainer, Marion A; Epstein, Lauren; Magill, Shelley S
Abstract: Background: Vancomycin is the most common antimicrobial drug administered to hospitalized patients, including children >90 days old, although the prevalence of β-lactam antibiotic resistance among Gram-positive pathogens is relatively low in children. Reducing inappropriate vancomycin use in children can reduce harm from antibiotic-associated adverse events and antimicrobial resistance (AR). We developed an approach to evaluating pediatric intravenous (IV) vancomycin prescribing quality using medical record data. Methods: Hospitals in three Emerging Infections Program (EIP) sites (CA, NM, and TN) were recruited to participate. Patients <18 years who received IV vancomycin in 2013 were identified through pharmacy records, excluding those on IV vancomycin solely for surgical prophylaxis. Trained EIP staff collected medical record data. We created a prescribing quality evaluation pathway using data on infection type, signs, symptoms, penicillin allergy, and AR risk factors. Clinically supported prescribing events were those with a positive culture for a Gram-positive organism with β-lactam resistance or unknown susceptibility; severe penicillin allergy; bone, joint, skin/soft tissue or central nervous system infection; pneumonia with AR risk factors; or events where vancomycin was stopped within 1 day of culture results for an oxacillin or penicillin/ampicillin-susceptible organism. Results: Sixty-five patients in 12 hospitals were evaluated. The median age was 7 years (interquartile range [IQR] 4–14), and median hospital stay was 7 days (IQR 3–16). The median vancomycin treatment length was 3 days (IQR 2–6); 41 patients (63%) received ≥3 days. Vancomycin use was clinically supported in 47 patients (72%) and unsupported in 18 (28%) (figure). Most unsupported use was for infections lacking microbiology data and for which vancomycin would not usually be indicated, such as pneumonia without AR risk factors (9/18, 50%). Conclusion: The use of IV vancomycin was not supported for >25% of children, indicating opportunities to improve prescribing and reduce unnecessary vancomycin use. Further analysis will utilize this prescribing pathway to evaluate the most recent prevalence survey data to identify areas to target stewardship interventions. Disclosures: All authors: No reported disclosures.